Clinicopathological and molecular characterization of chromophobe hepatocellular carcinoma. (15th June 2021) - Kang, Hyo Jeong; Oh, Ji‐Hye; Kim, Yeon Wook; Kim, Wonkyung; An, Jihyun; Sung, Chang Ohk; Kim, Jihun; Shim, Ju Hyun; Hwang, Shin; Yu, Eunsil; Heaphy, Christopher M.; Hong, Seung‐Mo
Abstract: Background and Aims: Chromophobe hepatocellular carcinoma (HCC) is a newly included subtype of HCC in the 5th edition of the WHO classification with distinctive histological features (chromophobic cytoplasm with anaplastic nuclei and pseudocyst formation) and is strongly associated with the alternative lengthening of telomeres (ALT) phenotype. However, the clinicopathologic characterization and molecular features of chromophobe HCC are unknown. Methods: To comprehensively characterize chromophobe HCC, whole exome sequencing, copy number variation, and transcriptomic analyses were performed in 224 surgically resected HCC cases. Additionally, telomere‐specific fluorescence in situ hybridization was used to assess ALT. These genomic profiles and ALT status were compared with clinicopathological features among subtypes of HCC, particularly chromophobe HCC and conventional HCC. Results: Chromophobe HCC was observed in 10.3% (23/224) cases and, compared to conventional HCC, was more frequent in females ( P = .023). The overall and recurrence‐free survival outcomes were similar between patients with chromophobe HCC and conventional HCC. However, chromophobe HCC displayed significantly more upregulated genes involving cell cycle progression and DNA repair. Additionally, ALT was significantly enriched in chromophobe HCC (87%; 20/23) compared to conventional HCC (2.2%, 4/178; P < .001). Somatic mutations in ALT‐associated genes, including ATRX, S MARCAL1, FANCG, FANCM, SP100, TSPYL5, and RAD52 were more frequent in chromophobe HCC (30.4%, 7/23 cases) compared to conventional HCC (11.8%, 21/178 cases; P = .024). Conclusions: Chromophobe HCC is a unique subtype of HCC with a prevalence of 10%. Compared to conventional HCC, chromophobe HCC is associated with female predominance and ALT, although overall and recurrence‐free outcomes are similar to conventional HCC.